Fluorofuroxans: Synthesis and Application as Photoinduced Nitric Oxide Donors. Issue 7 (30th May 2016) - Ando, Akihiro; Matsubara, Ryosuke; Takazawa, Saori; Shimada, Toshiyuki; Hayashi, Masahiko
Abstract: The synthesis of 3‐ and 4‐fluorofuroxans is reported for the first time. Under photoirradiation and physiological conditions, 4‐fluorofuroxans with weaker nitric oxide‐releasing ability are converted into 3‐fluorofuroxans, which show remarkable thiol‐mediated nitric oxide‐releasing properties, thereby suggesting that 4‐fluorofuroxans are potent photoinduced nitric oxide donors. Abstract : NO spells NO : 3‐ and 4‐fluorofuroxans have been synthesized for the first time. Under photoirradiation and physiological conditions, 4‐fluorofuroxans with weaker nitric oxide‐releasing ability are converted into 3‐fluorofuroxans, which show remarkable thiol‐mediated nitric oxide‐releasing properties, suggesting that 4‐fluorofuroxans are potent photoinduced nitric oxide donors.